Spillovers From the Rest of the World Into Sub-Saharan African Countries. (IMF Working Papers; Working Paper ;, 2009)
This paper investigates the impact of a global slowdown on individual African countries using a series of dynamic panel regressions for countries in the region, relating real growth in domestic output to world growth in trade weighted by partner countries and several control variables: oil prices, non-oil prices, financial variables, and country fixed effects. Estimates are then applied to prepare country-specific simulations. The model, which is shown to estimate well out-of-sample spillover effects in the region, shows that countries in the region are significantly affected by lower external demand for their exports, declines in commodity prices and the terms of trade, and tighter financial conditions abroad. The last, proxied by the spread of three-month Libor to US treasury bills, is to our knowledge one of the first applications of such a measure of financial conditions for countries in the region.